Some Compactness and Interpolation Results for Linear Boltzmann Equation. (7th September 2015) - Redjel, Nadjeh; Dehici, Abdelkader
Abstract : We discuss some compactness results inL p   ( 1 ≤ p < ∞ ) spaces related to the spectral theory of neutron transport equations for general classes of collision operators and Radon measures having velocity spaces as supports covering most physical models. We show in particular that the asymptotic spectrum of the transport operator is independent ofp .